Assessment as a Feedback Procedure in the Learning Community, with the Use of Web 2.0 Tools - Κουτσοσπύρου, Χριστίνα; Παπαδόγιαννη, Ελπινίκη; Μάνεσης, Νικόλαος (Education Sciences, 2018)
Through the example of evaluating the lesson “Educational Assessment”, in the School of Pedagogical and Technological Education, we investigated the importance of assessment/evaluation as a feedback procedure in the learning community that was created during the lessons. The students, soon to be teachers, stated, in the form of an observation diary with the use of Web 2.0 tools, their preliminary difficulties, the instructor’s teaching practices they believed that would be useful for their professional development, the emotions that appeared, their self-reflection from participating in this procedure and their suggestions. Processing the students’ data showed that self-reflection is a very important feedback procedure for the instructor and that assessment as feedback contributes to the effectiveness of teaching. Furthermore, the communication and the interaction between students and the instructor brought out the importance of cooperative learning in the learning community that was developed, as well as the development of New Technologies in teaching, with the use of active learning techniques of adult education.